1998
DOI: 10.1002/ana.410440125
|View full text |Cite
|
Sign up to set email alerts
|

Parallel loss of presynaptic and postsynaptic dopamine markers in normal aging

Abstract: Aging of the human brain is associated with a decline in dopamine (DA) function, generally interpreted as reflecting DA cell loss. Positron emission tomography studies revealed that in healthy individuals, the age-related losses in DA transporters (presynaptic marker) were associated with losses in D2 receptors (postsynaptic marker) rather than with increases as is known to occur with DA cell loss. This association was specific for DA synaptic markers, because they were not correlated with striatal metabolism.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
100
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(110 citation statements)
references
References 18 publications
9
100
0
1
Order By: Relevance
“…This is in accordance with existing in vitro and in vivo evidence of a significant decline in DRD2/3 density with age (Antonini et al, 1993;Ichise et al, 1998;Ishibashi et al, 2009;Rinne et al, 1990;Severson et al, 1982;Volkow et al, 1998;Wong et al, 1997). In addition, among our ADP, DRD3 blockade in the putamen and thalamus was negatively associated with age.…”
Section: D3 Receptors In Alcoholismsupporting
confidence: 93%
See 1 more Smart Citation
“…This is in accordance with existing in vitro and in vivo evidence of a significant decline in DRD2/3 density with age (Antonini et al, 1993;Ichise et al, 1998;Ishibashi et al, 2009;Rinne et al, 1990;Severson et al, 1982;Volkow et al, 1998;Wong et al, 1997). In addition, among our ADP, DRD3 blockade in the putamen and thalamus was negatively associated with age.…”
Section: D3 Receptors In Alcoholismsupporting
confidence: 93%
“…To explore whether PET outcome measures and other variables, such as drinking parameters, smoking parameters, and psychometric data, were related, multiple linear regression analysis with V T or D DRD3 V T (%) was included as the dependent variable. Age was also included as a covariate in these analyses as DRD2/3 levels decline with age (Antonini et al, 1993;Ichise et al, 1998;Ishibashi et al, 2009;Rinne et al, 1990;Severson et al, 1982;Volkow et al, 1998;Wong et al, 1997). To assess whether there was a significant V T blockade in the cerebellum, onetailed paired t-test for pre-vs post-blockade cerebellar V T values for each group was applied.…”
Section: Statisticsmentioning
confidence: 99%
“…Thus, slow recovery of TH, DA, and 5-HT systems from METH, coupled with the age-related decline in DA and 5-HT systems in GDNF Ï©/ÏȘ mice, may underlie the exacerbated motor deficits in GDNF Ï©/ÏȘ mice at 12 months of age. Exacerbated reduction in the function of the nigrostriatal DA system has consistently been associated with greater decline in motor function with aging in both humans (Suhara et al, 1991;Bannon et al, 1992;Volkow et al, 1998) and animals (Emborg et al, 1998;Hebert and Gerhardt, 1998;Cass et al, 2005;Yurek and Fletcher-Turner, 2001). …”
Section: Gdnfmentioning
confidence: 99%
“…It is well established that various aspects of dopaminergic modulation decline substantially during the course of usual aging (see BĂ€ckman et al, 2000;Volkow et al, 1998;see BĂ€ckman, Nyberg, Lindenberger, Li, & Farde, 2006 for recent review). Using the same experimental paradigm, we recently have shown that older adults, relative to younger adults, are less able to focus their attention on the attended ear; rather, their performance is primarily driven by the perceptual saliency of the auditory inputs (Passow et al, 2012a).…”
Section: Effects Of Dopamine Genes On Attentional Agingmentioning
confidence: 99%